Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Safe Neighborhood For Adolscent Girls; The Case Of Urban Dense Kampong In Yogyakarta City Center Mu’afifah & Setiawan Ceklik Reservoir Tourism Development with approach Eco-Waterfront Aulia Rohmah Ramadhani, Budi Prayitno & Wiwik Setyaningsih Early Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living Museum Ardelia J. Cungwin & Widjaja Martokusumo Improvement Strategy for KOTAKU program in Slum Settlements Area in Sidoarjo Ririn Putri Kusuma & Dian Rahmawati Urban Resilience: How to Apply in the Planning and Design Practice? Novi Maulida Ni’mah & Bakti Setiawan